THE PROTOCOL: INFLUENCE OF THE COMBINATION CARRIAGE СУР2С19*2 AND *17 ON EFFICACY OF CLOPIDOGREL - Е. М. Zelenskaya; О. L. Barbarash; V. I. Ganyukov; N. A. Kochergin; К. A. Apartsin; А. V. Gorokhova; S. А. Papeshina; К. Yu. Nikolaev; К. Yu. Batueva; S. V. Yankovskaya; А. V. Tronin; G. I. Lifshits (Российский кардиологический журнал, 2017)
Aim. To assess the association of efficacy and safety endpoints with simultaneous carriage of polymorphic variants of the gene CYP2C19: rs4244285 (*2), and rs12248560 (*17) in treatment with clopidogrel.Material and methods. In the study, 289 patients included, from large cities of Siberia, underwent coronary stenting for acute coronary syndrome. All participants were assessed for alleles CYP2C19*2, *3, *17, and clinical outcomes were followed for 30 days (thrombotic complications, bleedings).Results. It was found that simultaneous carriage of CYP2C19*2 and CYP2C19*17 alleles is associated with the risk of serious adverse events development of thrombotic origin comparing to the absence of such polymorphism carriage (p=0,016), and with general adverse events risk related to insufficiency of clopidogrel action (р=0,046).Conclusion. According to the study results, subjects with the *2/*17 carriage should be classified to a delayed clopidogrel metabolism group, as in the group definite and probable stent thrombosis were found significantly more prevalent.